Prognostic risk factors in upper gastrointestinal perforation: the role of body composition parameters - Zhu, Teng; Gu, Huayan; Chen, Yuefeng; Huang, Zeyuan; Hong, Wandong; Chen, Xiangjian (Frontiers in Nutrition, 2025)
BackgroundDespite medical advances, the prognosis for upper gastrointestinal perforation remained poor. The aim of our study was to identify predictors of adverse outcomes.MethodsWe retrospectively analyzed laboratory data from patients with upper gastrointestinal perforation at the First Affiliated Hospital of Wenzhou Medical University (January 2021–December 2023), categorizing them according to septic shock, intensive care unit (ICU) admission, and postoperative complications.ResultsUnivariate and multivariate analyses of 200 patients with upper gastrointestinal perforation identified predictors of a poor prognosis: low muscle reserve (OR = 3.82, 95% CI 1.36–10.71, p = 0.011), high visceral fat area (VFA) (OR = 3.54, 95% CI 1.16–10.80, p = 0.026), and platelet-to-lymphocyte ratio (PLR) (OR = 1.01, 95% CI 1.01–1.01, p = 0.048) predicted septic shock. Sex (OR = 0.22, 95% CI 0.06–0.78, p = 0.020), high VFA (OR = 4.84, 95% CI 1.38–17.02, p = 0.014), prothrombin time (PT) (OR = 1.54, 95% CI 1.09–2.18, p = 0.014), and D-dimer (OR = 1.16, 95% CI 1.01–1.34, p = 0.048) influenced ICU admission. Meanwhile, surgical approach (OR = 7.82, 95% CI 1.94–31.57, p = 0.004), maximum perforation diameter (OR = 1.08, 95% CI 1.02–1.15, p = 0.013), and white blood cell (WBC) count (OR = 0.88, 95% CI 0.78–0.99, p = 0.039) were linked to postoperative complications.ConclusionOur research found that the following factors were prognostic for upper gastrointestinal perforation: low muscle reserve, high VFA, PLR, sex, PT, D-dimer levels, surgical approach, WBC count, and perforation size.